Destruction of granite and concrete in water with pulse electric discharges - Боев С. Г. Сергей Григорьевич; Vazhov (Vajov) V. F. Vladislav Fedorovich; Левченко В. Г. Виктор Григорьевич; Muratov V. M. Vasily Mikhailovich; Zhgun (Jgun) D. V. Dmitry Vladimirovich; Adam A. M. Albert Martynovich; Uemura K. Kazunori (1999, 1999)
Title screen